2014
DOI: 10.1007/s00192-014-2355-4
|View full text |Cite
|
Sign up to set email alerts
|

Short-term outcomes of Altis® single-incision sling procedure for stress urinary incontinence: a prospective single-center study

Abstract: The Altis sling is a safe and effective SIS procedure for the treatment of SUI with a short-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
20
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 28 publications
6
20
0
1
Order By: Relevance
“…The subjective cure rate and objective cure rate was 82.0%, 92.5% in 6-month follow-up and 82.3%, 91.2% in 12 month follow-up respectively. The success rates of our study are comparable with previous studies in the literature, which reported similar patientreported and objective success rates of 80-91% in various countries, with varying cohort sizes and lengths of follow-up (6-12 months) [7,8,[11][12][13][14][15][16][17][18][19]. Evidence of longer-term outcomes for the adjustable anchored SIMS is now emerging.…”
Section: Commentssupporting
confidence: 92%
See 2 more Smart Citations
“…The subjective cure rate and objective cure rate was 82.0%, 92.5% in 6-month follow-up and 82.3%, 91.2% in 12 month follow-up respectively. The success rates of our study are comparable with previous studies in the literature, which reported similar patientreported and objective success rates of 80-91% in various countries, with varying cohort sizes and lengths of follow-up (6-12 months) [7,8,[11][12][13][14][15][16][17][18][19]. Evidence of longer-term outcomes for the adjustable anchored SIMS is now emerging.…”
Section: Commentssupporting
confidence: 92%
“…There were no significant perioperative complications such as bladder perforation, major bleeding requiring blood transfusion, hematuria or bowel injury in the present series, which was in agreement with other series of Ajust [11,13,16,20]. We considered that the absence of major complications in this series was attributable to reduction of the main risk factors; namely, reduction in blind passage of needles, the need for only one incision, and the relatively small extent of tissue dissection.…”
Section: Commentssupporting
confidence: 91%
See 1 more Smart Citation
“…There was no consistent method of presenting the assigned CTS codes. Some reported summaries or general descriptions of assigned codes [3,16,21,25], whereas others specified both the unique CTS codes and the number of patients assigned codes [2,4,5,14,15,[17][18][19][20][22][23][24]. One publication assigned codes to the cohort upon initial presentation and again following prosthesis/graft removal [5].…”
Section: Resultsmentioning
confidence: 99%
“…The Altis ® (Coloplast) is an adjustable single-incision sling made of type-1 macroporous polypropylene mesh measuring 7.75 cm [38]. It has low elasticity (7.5%), which allows the maintenance of integrity under tension and two anchors, one static and one bidirectional, that allow intraoperative tension adjustment.…”
Section: Altismentioning
confidence: 99%